Tomato Transcription Factor SlWUS Plays an Important Role in Tomato Flower and Locule Development - Li, Hui; Qi, Mingfang; Sun, Meihua; Liu, Ying; Liu, Yudong; Xu, Tao; Li, Yanbing; Li, Tianlai (Frontiers in Plant Science, 2017)
Tomato is a model species for fleshy fruit development. The shapes and sizes of tomato (Solanum lycopersicum L.) are mainly controlled by several loci, including locule number (lc). Two SNPs were found downstream of WUSCHEL (SlWUS) in a putative tomato CArG cis-regulatory element. The lc mutation may affect the binding of AGAMOUS(AG), cause the up-regulation of SlWUS and result in increased locule numbers. In this study, tissue expression levels showed that SlWUS is expressed in young floral buds and shoot apexes. Silencing SlWUS on an lc mutant genetic background with an RNA interference (RNAi) strategy resulted in smaller flowers and fruit than those of the wild-type plants, with decreased locule number. Further study revealed that the SlWUS RNAi lines exhibited altered expression levels of the TAG1 and SlCLV3 genes that participate in the regulation of tomato flower and fruit locule development. In conclusion, this study provides the first genetic evidence that SlWUS may be the candidate gene of the lc locus and reveals the function of SlWUS in flower development.